Pendampingan untuk Pengelolaan Web Profile Organisasi Koperasi Wanita Pengusaha Indonesia (KOWAPI) cabang Bengkayang - p, noviyanti; Mira, Mira; Sari, Maya (STMIK Royal, 2023)
Service activities at the Indonesian Women Entrepreneurs Cooperative Organization or usually abbreviated as KOWAPI are continuous service activities from previous service activities in 2022. The 2022 service focuses on creating a web profile for the KOWAPI organization. Based on the problems that partners are currently experiencing, namely a lack of understanding regarding digitalization and website literacy, the KOWAPI organization requested that the Shanti Bhuana Institute lecturers return to carrying out service that focuses on assistance in managing the existing web profile. Mentoring activities are carried out so that the KOWAPI organization's web profile can continue to be updated, so that it can help the development of the organization. The assistance provided focuses on creating news content, managing the website dashboard, and updating the home dashboard by including video content and photos of KOWAPI organizational activities. Keywords: mentoring; web managing; kowapi; service. Abstrak: Kegiatan pengabdian di Organisasi Koperasi Wanita Pengusaha Indonesia atau biasa disingkat KOWAPI merupakan kegiatan pengabdian berkelanjutan dari kegiatan pengabdian sebelumnya di tahun 2022. Pada pengabdian tahun 2022 berfokus pada pembuatan web profile untuk organisasi KOWAPI. Berdasarkan permasalahan yang mitra alami saat ini, yaitu kurangnya pemahaman berkaitan dengan digitalisasi dan literasi website, organisasi KOWAPI meminta agar pihak Dosen Institut Shanti Bhuana kembali melakukan pengabdian yang berfokus pada pendampingan dalam pengelolaan web profile yang sudah ada saat ini. Kegiatan pendampingan dilakukan agar web profile organisasi KOWAPI dapat terus diupdate, sehingga dapat membantu untuk perkembangan organisasi tersebut. Pendampingan yang dilakukan berfokus pada pembuatan konten berita, pengelolaan dashboard website, dan update dashboard beranda dengan memasukkan konten video dan foto-foto kegiatan organisai KOWAPI. Kata kunci: pendampingan; pengelolaan web; kowapi; pengabdian.